2018
DOI: 10.1186/s12957-018-1345-2
|View full text |Cite
|
Sign up to set email alerts
|

Rising global burden of breast cancer: the case of sub-Saharan Africa (with emphasis on Nigeria) and implications for regional development: a review

Abstract: BackgroundDespite mortality from breast cancer in Africa being higher than in high income countries, breast cancer has not been extensively studied in the region. The aim of this paper was to highlight the rising burden of breast cancer with an emphasis on sub-Saharan Africa as well as trends, characteristics, controversies and their implications for regional development.MethodologyA review of published studies and documents was conducted in Medline, Scopus, Pubmed and Google using combinations of key words-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
221
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(226 citation statements)
references
References 39 publications
5
221
0
Order By: Relevance
“…Physicians and nurses ranked educational/training programs as their highest-priority need, but physicians ranked training programs conducted in Africa higher than programs involving training in the US individuals and European individuals 6 ; as longevity increases with improvements in general medical resources, and as Western lifestyles and diets are adopted in Africa, breast cancer burden rises. [2][3][4] International initiatives featuring investment of resources into cancer services in Africa are therefore important but should be aligned with needs defined by local clinicians and other relevant stakeholders, such as the patient and advocacy communities and local and national governing bodies. This study demonstrated that African physicians and nurses prioritize provision of educational/training programs and medical/hospital supplies over direct monetary contributions.…”
Section: African Clinicians' Prioritization Of Needs In Internationalmentioning
confidence: 99%
“…Physicians and nurses ranked educational/training programs as their highest-priority need, but physicians ranked training programs conducted in Africa higher than programs involving training in the US individuals and European individuals 6 ; as longevity increases with improvements in general medical resources, and as Western lifestyles and diets are adopted in Africa, breast cancer burden rises. [2][3][4] International initiatives featuring investment of resources into cancer services in Africa are therefore important but should be aligned with needs defined by local clinicians and other relevant stakeholders, such as the patient and advocacy communities and local and national governing bodies. This study demonstrated that African physicians and nurses prioritize provision of educational/training programs and medical/hospital supplies over direct monetary contributions.…”
Section: African Clinicians' Prioritization Of Needs In Internationalmentioning
confidence: 99%
“…For example, only 32% of the women are still alive five years after a breast cancer diagnosis in sub-Sahara Africa as compared to 81% in the USA [6]. Again, Africa is reported to have the highest age-standardized mortality rates of breast cancer in the world even though the incidence rates are lower in Africa as compared to Western countries [7]. The increase in breast cancer incidents and mortality, especially in developing countries, has been attributed partly to the increasing population and the increased prevalence of risk factors associated with economic transition and the certain infectious agents of importance in cancer etiology [8].…”
Section: Introductionmentioning
confidence: 99%
“…It starts in a milk passage (a duct), breaks through the wall of the duct and invades the tissue of the breast [302]. In US, 232,000 new cases of breast cancer were diagnosed [303] and claimed the lives of 40,290 women [304] in 2015. First-degree relatives of patients with breast cancer have a 2-fold to 3-fold excess risk for development of the disease [305].…”
Section: Breast Cell Carcinomamentioning
confidence: 99%